Injury Characteristics in Pre-Professional Modern Dancers: Prospective Study of Differences Due to Sex, Training Year, and External Causal Mechanisms. Issue 2 (June 2021) - Bronner, Shaw
As efforts to improve surveillance and decrease injury rates in pre-professional dancer's progress, it is important to identify injury patterns and contexts. The aim of this study was to examine sex, training-based injury characteristics, and external causal mechanisms of injury among pre-professional modern dancers. Using a prospective cohort study design, 180 dancers (females = 140, males = 40, age 18.15 ± 0.68 years) were screened at freshman enrollment and followed for the 4 years of their college training. Injury, defined as medical attention injury (MAI) or time-loss injury (TLI), was classified by diagnosis, tissue category, body region, and incident event (action and dance environment). Negative binomial log-linear analyses evaluated injury rates by sex and training year. Multinomial regression compared injury characteristics and incident events, p < 0.05. Sex characteristics differed in height, mass, years of dance training, and previous injury (p < 0.037). Total, traumatic, and overuse injuries per 1, 000 hours decreased across training years for both injury definitions, p < 0.001, with no sex differences. In year 1, dancers were more likely to sustain muscle, tendon, and bone injuries (p < 0.008) and to injure leg, ankle, foot, and hip, thigh, and knee regions (p < 0.001). Jumping and running was the most commonly cited action mechanism in MAI and TLI in both sexes. Females were more likely to report alignment in MAI and TLI and jumping and running in TLI. Males were 1.4 times more likely to sustain muscle or tendon MAI (p = 0.006), while reporting partnering in MAI. Ballet class and rehearsals accounted for the majority of attributed dance environment mechanisms in MAI and TLI. Injury rates in pre-professional modern dancers decreased with training. Understanding sex, training, and external causal mechanisms will allow teachers to tailor programs to reduce injuries during training.